COMPUTERIZED MODEL OF RISK MANAGEMENT IN BUSINESS - Petrişor MANDU (Journal of Defense Resources Management, 2011)
The occurrence of risk situation and the manager’s awareness of it are serious threats for the organization and its objectives. Consequently, the manager has to have available, analyze, select and interpret many pieces of information, under stress, before making a decision for avoiding a disaster. Under these circumstances, a computerized model of risk management is the most adequate solution to make the intervention possibilities effective through a quicker and more accurate intervention. The model offers enough confidence and a favorable psychological state for managing risk. In accordance with this model, the risk manager processes the information by means of some operational (mathematical) methods and that favors reaching optimum solutions in the shortest delay, based on some estimated anticipations through a rational model.